Biofilm en Endodoncia: una revisión - Zambrano de la Peña, Sonia (2016)
It is demonstrated the efforts made endodontic microbiology and science to get to decipher the secrets of this unique structure although every day new questions arise. We need the treatments we use to combat biofilm achieve oxygenate the periapical ecosystem and basically scrape and loosen the tightly adhering bacteria Knowing the process of biofilm formation, microbial metabolism and strategies that they use to resist and remain hidden but active , we know why we observe refractory periapical lesions.